Manifestations of Non‐Planar Adsorption Geometries of Lead Pyrenocyanine at the Liquid‐Solid Interface. Issue 10 (19th July 2013) - Mali, Kunal S.; Zöphel, Lukas; Ivasenko, Oleksandr; Müllen, Klaus; De Feyter, Steven
Abstract In this work, we provide evidence for multiple non‐planar adsorption geometries of a novel pyrenocyanine derivative at the liquid–solid interface under ambient conditions. When adsorbed at the organic liquid–solid interface, lead pyrenocyanine forms well‐ordered monolayers that exhibit peculiar non‐periodic contrast variation. The different contrast of the adsorbed molecules is attributed to dissimilar adsorption geometries which arise from the non‐planar conformation of the molecules. The non‐planarity of the molecular backbone in turn arises due to a combination of the angularly extended pyrene subunits and the presence of the large lead ion, which is too big to fit inside the central cavity and thus is located out of the aromatic plane. The two possible locations of the lead atom, namely below and above the aromatic plane, could be identified as depression and protrusion in the central cavity, respectively. The manifestation of such multiple adsorption geometries on the structure of the resultant monolayer is discussed in detail. The packing density of these 2D arrays of molecules could be tuned by heating of the sample wherein the molecular packing changes from a low‐density, pseudo six‐fold symmetric to a high‐density, two‐fold symmetric arrangement. Finally, a well‐ordered two‐component system could be constructed by incorporating C60 molecules in the adlayer of lead pyrenocyanine at the liquid–solid interface.